1997
DOI: 10.1002/(sici)1097-0215(19971219)74:6<630::aid-ijc13>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the ratio of free to total prostate-specific antigen in serum

Abstract: The ratio of free prostate‐specific antigen (f‐PSA) to total PSA (t‐PSA) in serum, calculated as percent free PSA (f‐PSA%), is lower in patients with prostate carcinoma (PCa) than in patients with benign prostate hyperplasia (BPH). This parameter facilitates discrimination between the 2 groups of patients, but there is an overlapping of data. A better understanding of factors influencing this ratio is of practical importance. Therefore, f‐PSA% was measured in controls and patients suffering from BPH, PCa and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
2
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 18 publications
5
35
2
2
Order By: Relevance
“…26,27 The use of the FT ratio within patients, e.g., to assess preoperatively the pathologic stage or monitor disease progression, is less well established. 28,29 In our study, no FT ratio treatment effect was found (data not shown).…”
Section: Ratio Of Free and Total Psacontrasting
confidence: 55%
“…26,27 The use of the FT ratio within patients, e.g., to assess preoperatively the pathologic stage or monitor disease progression, is less well established. 28,29 In our study, no FT ratio treatment effect was found (data not shown).…”
Section: Ratio Of Free and Total Psacontrasting
confidence: 55%
“…The interobserver and intraobserver variation of 13-15% did not differ from that found in earlier investigations. 35 All men underwent DRE. A DRE finding that was nonsuspicious for carcinoma was defined as negative, and a finding that was suspicious for carcinoma was considered positive.…”
Section: Methodsmentioning
confidence: 99%
“…Small pieces of tissue were dissected immediately after removal of the prostate and stored in liquid nitrogen until analysis. Histological analysis from all the tissue pieces was performed as described previously (31) to ensure that the tissue was either malignant or benign. The tissues were pulverized with a hammer under liquid nitrogen, and RNA was extracted as described above, using Trizol reagent.…”
Section: Methodsmentioning
confidence: 99%